2012
DOI: 10.1089/end.2011.0406
|View full text |Cite
|
Sign up to set email alerts
|

The Ureteroscope as a Safety Wire for Ureteronephroscopy

Abstract: Using the ureteroscope as the safety mechanism, ureteroscopy is safe with regard to maintaining renal access and control. Routine safety wires during ureteronephroscopy are not necessary assuring the ureteroscope is in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…6 Two other groups reported independently their results of semi-rigid and flexible URS for the treatment of stone disease without an SGW. 5,9 Eandi et al 9 reported no intraoperative complications related to lack of a safety wire over 322 semi-rigid and flexible URS performed for the treatment of urolithiasis. Patel et al 5 described their experience with flexible URS for the treatment of calyceal and pelvic stones on 268 patients with the use of a working wire alone.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…6 Two other groups reported independently their results of semi-rigid and flexible URS for the treatment of stone disease without an SGW. 5,9 Eandi et al 9 reported no intraoperative complications related to lack of a safety wire over 322 semi-rigid and flexible URS performed for the treatment of urolithiasis. Patel et al 5 described their experience with flexible URS for the treatment of calyceal and pelvic stones on 268 patients with the use of a working wire alone.…”
Section: Methodsmentioning
confidence: 99%
“…5,9 Eandi et al 9 reported no intraoperative complications related to lack of a safety wire over 322 semi-rigid and flexible URS performed for the treatment of urolithiasis. Patel et al 5 described their experience with flexible URS for the treatment of calyceal and pelvic stones on 268 patients with the use of a working wire alone. In all, 20% of the patients needed ureteral dilation, and 15% had a ureteral access sheath placed intra operatively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations